Relationship between the efficacy of sulfonylurea therapy and structural variants of the ABCC8 (rs757110) and KCNJ11 (rs5219) genes in patients with type 2 diabetes mellitus with different phenotypes - I. А. Bondar’; М. L. Filipenko; О. Yu. Shabel’nikova; Е. А. Sokolova (Сибирский научный медицинский журнал)
Recently, a large number of studies have been conducted to investigate the variability of response in the treatment of diabetes mellitus (T2DM), which make personalized medicine possible. However, the available data are insufficient to decide on the choice of sugar-lowering drugs in T2DM. The search for phenotypic and clinical factors of pharmacogenetic response to therapy continues. Aim of the study was to investigate the relationship between the effectiveness of sulfonylurea therapy and structural variants of the ABCC8 (rs757110) and KCNJ11 (rs5219) genes in T2DM patients with clinical phenotypes. Material and methods. A cross-sectional clinical and pharmacogenetic study of 1271 patients with T2DM receiving sulfonylurea monotherapy (SU) or in combination with metformin and divided into three clinical phenotypes: with insulin deficiency (insulinopenic phenotype), with obesity and moderate insulin resistance (classical phenotype) and with severe insulin resistance (insulin-resistant phenotype) was performed. A glycated hemoglobin content of less than 7% was considered as a good response to SU therapy. Results. Patients with a good response to SU therapy with a classic phenotype had a longer duration of diabetes compared to patients with absence of good response (5.68 ± 5.22 vs 9.12 ± 6.10 years, respectively, p < 0.001) and a later age at diagnosis of T2DM (54.05 ± 7.18 vs 49.37 ± 7.65 years, respectively, p < 0.001); patients with an insulin-resistant phenotype had T2DM established at an older age (54.35 ± 7.91 vs 50.10 ± 7.51 years, respectively, p = 0.001). Logistic regression analysis did not reveal a statistically significant association of the genotype of the structural variant of the ABCC8 gene (rs757110) with the effectiveness of SU in clinical phenotypes. The T/T genotype of the KCNJ11 gene (rs5219) was associated with a better response to SU therapy only in the group of T2DM patients with the classic phenotype (odds ratio 1.85, 95% confidence interval 1.05–3.25, p = 0.041). Conclusions. In patients with type 2 diabetes, predictors of a good response to SU with a classic phenotype were a later age of T2DM diagnosis, a shorter duration of diabetes, and the presence of the T/T genotype of the structural variant of the KCNJ11 gene (rs5219); with an insulin-resistant phenotype, a later age of T2DM diagnosis; with the insulinopenic phenotype no clinical and genetic predictors of the SU effectiveness were identified.